Experimentally Observed Imitation and Cooperation in Price Competition on the Circle - Reinhard Selten; José Apesteguia (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
This paper reports an experiment on a location game, the so-called "Price-Competition on the Circle." There are n symmetric firms equidistantly located on a circle. Consumers are uniformly distributed. Each consumer buys one and only one unit from that firm whose price, including the cost of transportation, is the lowest, provided such a price is below a maximum willingness to pay. Experiments, extended over 200 periods, were run with 3, 4, and 5 participants. Subjects did not receive any information about the relationship between prices and profits, but they received feedback on prices and profits of two neighbors after each period. The evaluation compares predictions derived from imitation equilibrium (Selten and Ostmann 2001) and Cournot equilibrium, as well as symmetric joint-profit maximization. The results qualitatively favor imitation equilibrium, as long as no cooperation is observed.
Keywords: R32; L13; C92; C72; 330; Imitation; Cooperation; Location; Experiments; Imitationswettbewerb; Räumliche Preistheorie; Experiment; Nash-Gleichgewicht; Nichtkooperatives Spiel; Theorie